Remittances and financial inclusion in development - Helen S. Toxopeus; Robert Lensink (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
In this paper we focus on the relationship between remittance inflows and financial inclusion in developing countries. We present single equation estimates on remittances and financial inclusion, and system estimates in which economic growth is explained by e.g., financial inclusion, and financial inclusion by, e.g., remittances inflows. These regressions clearly confirm our main hypothesis that remittances have a development impact through their effect on financial inclusion. Overall, our paper indicates the importance of studying the effects of remittances in developing countries. Remittances, in terms of size, are not only one of the main capital inflows in developing countries, often even more substantial than ODA, but they also appear to have a robust positive effect on economic growth.
Keywords: F24; G21; 330; capital flows; remittances; finance; Rücküberweisung (Migranten); Bankgeschäft; Entwicklungsländer